Improving the performance of flexibility and coordination abilities university girls-students in the process of hatha-yoga classes during the university year - Толчєва Ганна Вікторівна, (Ganna Tolchieva) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to determine the results of changes in terms of flexibility and coordination abilities of university students in the process of hatha-yoga developed by the program during the year. Material and methods: a pedagogical experiment was attended by 60 students of the university at the age of 17–20 years. Conducted pedagogical experiment and educational testing, the results were processed by methods of mathematical statistics. Results: the control group students only attended university studies in physical education, experimental – three times a week, hour and a half fitness classes on hatha-yoga. Conclusions: in the pedagogical experiment proved the effectiveness of the developed program on hatha-yoga in extracurricular work of students of the university; the average results recorded characteristics of flexibility and coordination abilities of university students and calculated at the end of the university year, the percentage improvement in these indicators